2022
DOI: 10.3389/fendo.2022.834207
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Investigations of Intracranial Atherosclerosis Using Multiple Hypercholesterolemic Rabbit Models

Abstract: BackgroundIntracranial atherosclerosis (ICAS) is one of the most common causes of ischemic stroke, but there are few animal models that can recapitulate its pathological features. In this study, we examined ICAS pathological features and anatomic distributions using three types of hyperlipidemic rabbit models. We also investigated the effect of different lipoprotein profiles and hypertension on ICAS.Materials and MethodsWe examined Watanabe heritable hyperlipidemic (WHHL) rabbits, apoE knockout (KO) rabbits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Different types of hyperlipidemia may have different arterial preferences for atherosclerosis. Intracranial atherosclerosis of apoE KO rabbits was reported in previous studies ( 37 , 38 ). Intracranial atherosclerosis was developed in apoE rabbits fed a CRD but WHHL rabbits, a model for human FH, exhibited more severe lesions than apoE KO rabbits.…”
Section: Discussionsupporting
confidence: 66%
“…Different types of hyperlipidemia may have different arterial preferences for atherosclerosis. Intracranial atherosclerosis of apoE KO rabbits was reported in previous studies ( 37 , 38 ). Intracranial atherosclerosis was developed in apoE rabbits fed a CRD but WHHL rabbits, a model for human FH, exhibited more severe lesions than apoE KO rabbits.…”
Section: Discussionsupporting
confidence: 66%
“…However, a notable caveat in this study is that most ApoE-KO rabbits were fed an atherogenic diet. 34 By contrast, a subsequent study by Tang et al 32 evaluated differences between WHHL and ApoE-KO rabbits and found that WHHL animals develop more severe ICAD than ApoE-KO animals. This study further demonstrated that the induction of hypertension exacerbates ICAD in WHHL animals.…”
Section: Small Animal Modelsmentioning
confidence: 96%
“…This study further demonstrated that the induction of hypertension exacerbates ICAD in WHHL animals. 32 The Tang group identified smooth muscle cells and infiltrating macrophages as the major components of the atherosclerotic lesions in both models, and they observed that lesions occurred mainly at bifurcations of the posterior cerebral artery, basilar artery, and vertebral artery. 32 While these rabbit models show evidence of lesions in a wider variety of intracranial arteries than other small animal models, they do not seem to recapitulate ICAD in more distal arteries like the ICA and MCA, which are often affected in human patients.…”
Section: Topical Reviewmentioning
confidence: 99%